Presenting a Model for the Evaluation of the Quality of e-learning at Payam Noor University - Sedighe Zamani Roodsari (The Journal of Quality in Education)
The current study aims to design a quality evaluation model of the electronic education system at Payam Noor University by applying a mixed methodology. The statistical population of the qualitative section includes twelve professors, researchers, and experts in the field of e-learning, who were selected by selective sampling. The conceptual model of the research was collected after conducting in-depth semi-structured interviews. The quantitative data based on a questionnaire designed by the researcher was collected from 274 professors and students with experience teaching or studying in the electronic education system of Payam Noor University. The data was analyzed using the structural equation modeling method in PLS3 software. The research results show that quality is a concept consisting of four categories behavioral, scientific, cognitive ability, and virtual learning experience. The study’ findings also reveal that cultural, pedagogical, learner, communication, infrastructural, and institutional factors affect the quality of Payam Noor University's electronic education system. Also, the results show that these characteristics will help universities achieve the four outcomes of competitiveness, job opportunities, economy, and reputation by establishing a quality education system. The ideal model for evaluating the quality of e-learning at Payam Noor University is a process approach in which the three dimensions of factors, quality indicators, and outputs are examined and measured. In other words, electronic education is successful when it can create a valuable experience of virtual education while empowering the learners scientifically, behaviorally, and cognitively to let all the stakeholders of higher education benefit from a valuable electronic education.